Technoeconomic Analysis of Integrated Bioethanol from Elephant Grass (Pennisetum purpureum) with Utilization of Its Residue and Lignin - Safaat, Muhammad; Wulan, Praswasti Pembangun Dyah Kencana (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2022)
Abstract Bioethanol has been developed as an alternative biofuel. Elephant grass is one of the lignocelluloses that can be used as a source of bioethanol. The bioethanol fermentation process should be improved along with its economic competitiveness to promote its wider application. This study aims to investigate and to evaluate the best scheme of biethanol (standalone) and the combination of bioethanol and its by-products through technoeconomic analysis. The method used is collecting data from several previous studies and simulating it with SuperPro Designer. Data from flowsheeting simulation is used as economic simulation data using Microsoft Excel. The results of this study indicate that the processing of biogas and lignin waste as fuel and lignosulfonates can increase the economic value of the bioethanol production process. The best economic value is the bioethanol production process using biogas and lignin as fuel for a Biomass Power Plant which is called Pembangkit Listrik Tenaga Biomassa (PLTBm) with a Net Present Value (NPV) of IDR 364,358,976,036, Internal Rate of Return (IRR) 11.32%, Pay Back Period (PBP) 7.2 years, and Profitability Index (PI) 1.08Keywords: bioethanol, biogas, elephant grass, lignosulfonate, SuperPro Designer AbstrakBioetanol telah dikembangkan sebagai bahan bakar nabati alternatif. Rumput gajah merupakan salah satu lignoselulosa yang dapat digunakan sebagai sumber bioetanol. Proses fermentasi bioetanol harus ditingkatkan seiring daya saing ekonomi untuk mempromosikan penerapannya yang lebih luas. Tujuan studi ini adalah untuk menginvestigasi dan mengevaluasi skema terbaik bietanol (standalone) serta kombinasi bioetanol dan produk sampingnya melalui analisis teknoekonomi. Metode yang digunakan ialah melakukan pengumpulan data dari beberapa penelitian sebelumnya dan disimulasikan dengan SuperPro Designer. Data dari simulasi flowsheeting digunakan sebagai data simulasi ekonomi menggunakan Microsoft Excel. Hasil studi ini menunjukan bahwa pengolahan biogas dan limbah lignin sebagai bahan bakar dan lignosulfonat dapat meningkatkan nilai ekonomi dari proses produksi bioetanol. Nilai ekonomi yang paling baik adalah proses produksi bioetanol dengan pemanfaatan biogas dan lignin sebagai bahan bakar Pembangkit Listrik Tenaga Biomassa (PLTBm) dengan nilai Net Present Value (NPV) Rp 364.358.976.036-; Internal Rate of Return (IRR) 11,32%, Pay Back Periode (PBP) 7,2 tahun, serta Profitability Index (PI) 1,08.Kata kunci: bioetanol, biogas, lignosulfonate, rumput gajah, SuperPro Designer